Penile granuloma caused by liquid silicone injection - Ishandono Dachlan, Ishandono Dachlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Various alloplastic injectable implants have been developed for soft tissue augmentation withoutsurgery. Silicone is a polymer from a family of chemically related organo-silicone compounds that mayexist in any state from a fluid to a solid. Injectable liquid silicone has been used for various cosmetictreatments, mainly for soft tissue augmentation, for example lip, cheek, breast, buttock, and penile. Liquidsilicone has been implicated in variety of adverse inflammatory reactions, sometimes resulting in tissuedestruction.We describe an adverse granulomatous reaction after the injection of liquid silicone for penile augmentation.Penile granuloma can occur as an adverse effect of penile enlargement with the injection of high viscositysolution, like silicone (siliconoma), paraffin (paraffinoma), vaseline or mineral oil. Penile granuloma is arare case which needs an accurate management.We found 30-years old man that occurs 5 weeks after non medical injection of liquid silicone. Surgicalmanagement was done with an excision of the granuloma and round incision on the upper penile, exceptthe urethral part. There were no complications following the treatment. Histopathology examination showedthe appearance of silicone-like foreign body granuloma and fibrosis of the preputium.Â It is concluded that Injection liquid silicone for penile augmentation could cause adverse granulomatous.Â Surgical management can be done with an excision of the granuloma.Keywords: liquid silicone, penile granuloma, surgical excision.